Upper Airways Spray for Viral Infections Prevention - Beniamino Palmieri; Maria Vadalà (Journal of Immunology Research)
Aim. Several studies emphasized the antiviral properties of many natural compounds enclosed in nutraceuticals formulas and quite effective to prevent the respiratory infections. The rationale of our investigation has been to achieve protection from common cold viruses’ infection of the upper airways pooling together and dispensing different active principles on a multistep defense basis. Material and Methods. 30 patients affected by sudden aspecific viral-induced sore throat rhinitis were divided in two groups: (1) the first group included 15 patients which were administered with our spray formula and (2) the second group included 15 patients with the commercial nasal lavage kit. The mucous smear was stained with May Grunwald-Giemsa to exclude eosinophilic infiltrate and confirm the prevalence of granulocytes and lympho-monocytes typical of viral seasonal inflammatory upper airways conditions. Results. The symptomatic relieve is remarkedly evident in the treated group with our spray compared to the second group treated with commercial nasal lavage kit. Conclusions. The open case-control retrospective observational study showed a definite benefit of the spray based on natural herbal extracts to take control of the upper airways respiratory distress due to viral infections.